The regular solar wind impact on the high-latitude electron density in time scales of days and weeks - Borries, Claudia; Davies, Fredy; Iochem, Pelin; Tasnim, Samira; Vogt, Joachim (2023)
Global changes in the state of the ionosphere-thermosphere system depend to a large extent on the energy input from the solar wind and magnetosphere, which occurs in the high-latitude regions. On the one hand energy is deposited in the form of Joule heating causing changes in the thermosphere composition and circulation. On the other hand, imposed electric fields change plasma transport. Joule heating is closely related to changes in the solar wind dynamic pressure, because it can cause a compression of the magnetosphere driving currents in the magnetosphere, and the currents transfer electromagnetic energy into the ionosphere. The enhancement of plasma convection in the polar ionosphere is related to the intensification of the convection electric field, which is driven by the solar wind sweeping across the open magnetic field lines of the polar magnetosphere. These changes are most significant during storm conditions, caused e.g. by coronal mass ejections and corotating interaction regions. The storm related energy release in the high-latitude ionosphere is impacting the thermosphere-ionosphere system on a global scale. However, the solar wind impact causes a regular every day variability of the polar ionosphere, too. We are investigating how the solar wind variability in time scales of days and weeks is reflected in the ionosphere variability at Tromso, which is located in Scandinavia at 70°N, 19°E. We use cross correlation analysis of total electron content with solar wind merging electric field and dynamic pressure data. It can be shown that in timescales of days and weeks, the magnitude of correlation between TEC and solar wind reaches similar values to the correlation of TEC and F10.7. However, the results show that the correlation between TEC and solar wind parameters depends strongly on local time, season and solar cycle. There is a clear annual cycle in the variability of the correlation coefficient, with higher correlation values in winter than in summer. The positive correlation in winter close to ...